Barriers and facilitators perceived by registered nurses to providing person-centred care at the end of life. A scoping review. (13th November 2019) - Carvajal, Ana; Haraldsdottir, Erna; Kroll, Thilo; McCormack, Brendan; Errasti-Ibarrondo*, Begoña; Larkin, Philip
No abstract available